2015
DOI: 10.1142/s1084946715500193
|View full text |Cite
|
Sign up to set email alerts
|

Chance Non-Control and Entrepreneurship

Abstract: The personality of entrepreneurs can have a large influence on entrepreneurial startups. The general locus of control, which is an element of the personality of entrepreneurs, is considered to be critical for the creation of entrepreneurial startups. Despite the generally acknowledged importance of one’s locus of control for entrepreneurial intentions and new firm startups, a research gap exists because less emphasis has been given to external locus of control, in particular chance control. Chance non-control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Stewart and Roth’s (2001) meta-analysis showed that compared to managers, entrepreneurs tend to have a greater proclivity to take risks. However, this does not mean they have an extreme risk-taking propensity (De Vries, 1977); rather, entrepreneurs usually engage in moderate risk-taking (Antoncic et al, 2015). There are essentially three different theoretical frameworks on risk-taking (Byrnes et al, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Stewart and Roth’s (2001) meta-analysis showed that compared to managers, entrepreneurs tend to have a greater proclivity to take risks. However, this does not mean they have an extreme risk-taking propensity (De Vries, 1977); rather, entrepreneurs usually engage in moderate risk-taking (Antoncic et al, 2015). There are essentially three different theoretical frameworks on risk-taking (Byrnes et al, 1999).…”
Section: Literature Reviewmentioning
confidence: 99%